PENGARUH WORKPLACE INCIVILITY DAN JOB BURNOUT TERHADAP TURNOVER INTENTION PADA CV METALIK BARU - Rocky Rocky (Agora, 2018)
Human resources in the company is an important aspect for the company, where the company has Human Resource Development (HRD) department to coordinate and develop existing human resources on CV Metalik. The phenomenon that occurs in the CV. Metalik Baru is the employee turnover rate on CV Metalik Baru is high enough to be evident from employee turnover data obtained with high turnover rate from January to December 2017. One of the factors affecting turnover intention is workplace incivility. In addition, other factors that may affect turnover intention is the job burnout. The purpose of this research is to know the influence of workplace incivility and job burnout partially and simultaneously toward intention turnover at CV Metalik Baru. This research uses causality research design using quantitative method. Population Sample in this research is employees at CV Metalik Baru as many as 40 employees. The analytical technique used multiple linear regression. Based on the results of research and discussion it can be concluded that the workplace increment and job burnout variables partially and together affect the turnover intention on the CV. Metalik Baru. Then proven H1, H2, and H3 are accepted.